Les magazines de bandes dessinées : une approche médiatique et culturelle - Matthieu Letourneux; Yoan Vérilhac (Comicalités)
The history of comics has now taken into account the press media that contributed to the invention and development of this new mode of expression. However, a study of comics periodicals focused on media, journalistic and communication issues was still missing. It is therefore by first taking into account the logic specific to the world of periodicals that we must understand these publications and the way in which they determine the culture that is shaped, between 1930 and 2000, around comics, and even the language of comics itself. Seriality, serialization, periodicity, relationship with readership, positioning in publication systems and commercial spaces (kiosks, newsagents): all fundamental structures of the magazine economy that shape the ways of commenting on, creating and promoting comics. Then, by specifically observing the editorial or press-related parts: covers, sections, letters, advertisements, games, summaries, we reveal the inclusion of these magazines in various media series (youth newspapers, cultural press, glamour press, for example) and the cultural differences that have been assigned to them over the decades, from children’s entertainment to integration into the logic of consumption and advertising, including counter-cultural transgression.